Uji Waktu Rehidrasi Nasi Instan Fungsional Ekstrak Kurkumin (Curcuma domestica Val.) Sebagai Pangan Fungsional Berbasis Pangan Lokal - Umar Hidayat; Noralia Purwa Yunita; Agus Sudrajat (Lembaga Pengembangan Kinerja Dosen, 2023)
For the Indonesian people, rice is life. Rice is a staple food source for the majority of Indonesia's population. Based on the method of processing, several types of rice are known, including crushed rice, polished rice, milled rice, broken skin rice, head rice, instant rice, and parboiled rice. Rice quality includes market quality, physical quality, milled quality, cooking quality and nutritional quality. Until now, nutritional quality is still neglected. This is partly because the government is still focusing on efforts to increase rice production to meet the needs of the population. After rice self-sufficiency was achieved, driven by economic improvements and technological advances, the nutritional quality of rice began to receive attention. The success of economic development has brought consumers to a status that allows demands for higher quality rice to emerge.